NURSING PROTOCOL FOR GLYCEMIC MONITORING IN HOSPITALIZED INDIVIDUALS WITH TYPE 2 DIABETES MELLITUS - Frota, Gesiane Araújo; Silva, Denise Maria Guerreiro Vieira da; Ferreira, Darlisom Sousa; Arruda, Cecília; Ribeiro, Maria de Nazaré de Souza; Boell, Julia Estela Willrich; Ramos, Flávia Regina Souza (Cogitare Enfermagem, 2024)
Objective: Developing a nursing care protocol for glycemic monitoring of hospitalized individuals with Type 2 Diabetes Mellitus. Method: Methodological research conducted in 2021 and 2022 in Manaus, state of Amazonas, Brazil, in three phases: 1) Theoretical phase: literature review, consensus search, development of analytical frameworks, content selection. 2) Protocol development phase. 3) Protocol evaluation phase conducted by nurses regarding clarity, relevance, and applicability. Results: The literature review yielded 15 articles and five consensus statements from scientific societies. The protocol consists of 11 items, with an emphasis on the identification of risk factors, manifestations of hyperglycemia and hypoglycemia, nursing care, the nursing process, and a flowchart. The nurses’ evaluation was favorable, achieving an CVI of 1.0 regarding clarity and relevance, and it was considered applicable. Conclusion: The protocol will support nursing care in glycemic monitoring, enabling better glycemic control for hospitalized individuals with diabetes.